Aid effectiveness for poverty reduction: macroeconomic overview and emerging issues - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2009)
Following the adoption of the MDG, particulary the first one that is to reduce poverty by half between 1995 and 2015, numerous studies have examined how external aid can contribute to their achievement. The formula "doubling aid to reduce the poverty by half" relied on the implicit assumption that aid was an effective instrument for poverty reduction. The formula and corresponding assumption have of course been debated. Two opposite views have clearly appeared, one, well represented by Jeffrey Sachs in his End of Poverty, underlining the need for a big push to get low income countries out of poverty traps, the other one, exemplified by the attacks of William Easterly against aid, a big push and the idea itself of a poverty trap, but also including arguments about a limited absorptive capacity. Elsewhere we have argued that the absorptive capacity of aid depends on aid modalities and can be enhanced by a reform of aid, a point to which we will come back to later (Guillaumont and Guillaumont Jeanneney 2007). Document conjoint Cerdi / Ferdi
Keywords: O11; F35; 330